Thrombocytapheresis—An Effective Means for Management of Symptomatic Hyperthrombocytosis. (21st September 2018) - Jaitly, Vanya; Belousova, Tatiana; Klein, Kimberly; Tint, Hlaing; Castillo, Brian; Bai, Yu
Abstract: Objectives: Thrombocytosis occurs in varied clinical settings ranging from reactive to myeloproliferative disorders (MPDs). Symptomatic thrombocytosis can cause fatal ischemic and hemorrhagic complications. Although cytoreduction with medication remains the primary therapy, many times patients are emergently admitted for symptoms. We report two cases with symptomatic thrombocytosis of unknown etiology where thrombcytapheresis proved an invaluable option for rapid reduction of life-threatening ischemia. Methods: Case 1: A 61-year-old female with a history of hypertension was admitted for ischemic stroke and platelet count of 1.49 million/mcL (microliter). Multiple infarcts in left middle cerebral artery distribution and right cerebellum were noted on imaging. Case 2: A 37-year-old female with a history of spontaneous splenic rupture 2 months ago status post splenectomy presented with splenic, superior mesenteric, and portal vein thrombosis and thrombocytosis. Underlying etiology was not known in both cases. Results: Case 1: The patient's acute stroke was thought to be associated with thrombocytosis. An urgent thrombocytapheresis was performed; 73% of platelets were removed after one procedure with significant neurological improvement. She was started on hydroxyurea thereafter and discharged pending further workup for MPD. The patient was lost to follow-up. Case 2: Platelet count was 2.39 million/mcL on admission. Two platelet reduction procedures were performed, the first one being unsuccessful owing to technical difficulties; 82% of preprocedure platelets were removed, reducing the count from 2.084 million/mcL to 402 K/mcL. Patient was started on anticoagulants and hydroxyurea as bone marrow aspiration was suspicious for MPD. Conclusion: Extreme thrombocytosis can lead to fatal ischemic complications. Thrombocytapheresis is an efficient and rapid means of urgent platelet reduction and is useful as a bridging therapy in patients with unknown etiology until workup is complete or before cytoreductive therapy is started or takes effect.